Kepastian Hukum Mengenai Penetapan Tersangka Untuk Kedua Kalinya Oleh Penyidik Pemberantasan Korupsi - Prasetiyo, Leo Dwi; Aji, Rihantoro Bayu (Universitas Wijaya Putra, 2024)
The background of writing this journal article is the second time the determination of a suspect against Ilham Arief Sirajjudin (Petitioner), the former mayor of Makassar by investigators from the Corruption Eradication Commission (KPK). Previously, the Corruption Eradication Commission named the Petitioner as a suspect, but the Corruption Eradication Commission lost in pretrial because it named the Petitioner as a suspect but did not fulfill at least 2 valid pieces of evidence according to the Criminal Procedure Code. Therefore the pretrial judge granted the Petitioner's request and declared the KPK's determination of the suspect invalid with decision number 32/Pid.Prp/2015/Pn.Jkt.Sel on (Pretrial volume 1). Then, after the Pretrial Appellant was granted by the pretrial judge, several days later, the KPK again named the Petitioner as a suspect. However, the Petitioner again carried out pretrial efforts with one of his petitions namely that the Petitioner had won in the previous pretrial and the decision was final and binding on all parties, so if the KPK again named the Petitioner as a suspect it would create legal uncertainty for the Petitioner. However, in pretrial volume 2, the pretrial judge did not grant the Petitioner's request on the grounds that the KPK had determined the Petitioner according to procedure. And finally the Judge rejected the Petitioner's Pretrial with decision number 55/Pid.Prp/2015/Pn.Jkt.Sel. In the Pretrial Decision of the South Jakarta District Court Number: 32/Pid.Prp/2015/Pn.Jkt.Sel and 55/Pid.Prp/2015/Pn.Jkt.Sel there are two legal issues that the author will raise in this journal article In this case, the first problem is related to the determination of a suspect for the second time by Corruption Eradication Commission investigators against someone whose pretrial has been granted in relation to the principle of legal certainty. The second legal issue is related to the principle of Ne bis in idem in the Criminal Code which is linked to decisions Number: 32/Pid.Prp/2015/Pn.Jkt.Sel and 55/Pid.Prp/2015/Pn .Jkt.Sel regarding the determination of the suspect for the second time against someone. The purpose of writing a journal article to be achieved is to analyze the determination of a suspect for the second time by KPK investigators against someone who has been granted a pretrial based on the principle of legal certainty. Then the second objective is to analyze the existence of the Ne Bis In idem principle in the Criminal Code by pretrial decision regarding the determination of the suspect to return for the second time against someone. The conclusions drawn based on the writing of this journal article are first, the determination of a suspect for the second time against someone who has been granted pretrial by KPK investigators does not conflict with the principle of legal certainty, because pretrial is purely administrative or formal in nature. Therefore, if the investigator is still convinced that the person has committed a crime, the investigator can re-establish that person as a suspect through the correct legal procedures. The second conclusion, the principle of ne bis in idem in the Criminal Code does not apply to pretrial decisions regarding the determination of a suspect for the second time against someone, because pretrial is administrative (formal) in nature, namely it only has the authority to examine and decide legal matters, not forced efforts and provide protection of human rights in a person at the level of investigation and prosecution and not examining matters at the time of trial or the main case.